Tourist Loyalty Model in Local Culinary Selection in the Era of the Covid 19 Pandemic in Palembang City - Setiawan, Heri; Rini; Bustan, Jusmawi; Maretha, Fetty; Africano, Fernando (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose –Local food and tourism are the main components that determine tourist behavior. Key attributes of local food such as taste, quality, appearance, environment and employee behavior may vary from country to country. Local food plays an important role in determining the overall tourist experience of the destination.The purpose of this research is to develop a conceptual model to determine the loyalty of tourists in choosing local culinary. Methodology/approach –The population of this research is tourists who come to culinary tourism destinations in Palembang City at the time the survey was conducted. Convenience sampling method was used to determine the research sample. The sample in this study were 168 respondents. On researchdata analysis technique using SEM AMOS. Findings –This study explains that the quality of personal interaction and service quality have a positive and significant effect on tourist satisfaction. Tourist satisfaction has a positive and significant effect on tourist loyalty. Novelty/value –BBased on a review of various literatures related to this study, there has been no research in the field of tourism marketing that integrates the concepts of food quality, personal interaction quality, environmental quality, perceived value and service quality that were developed together to measure tourist satisfaction and the concept of tourist satisfaction. to measure tourist loyalty.